THE RELATIONSHIPS BETWEEN THE PERCEPTION OF HONOR IN RELATED TO WOMEN, VALUES AND SEX ROLES - Fatma Gül CİRHİNOĞLU (Fırat University, 2019)
Objective of this study is to determine the relationships among honor perception attributed to women, values and sex roles. Sample group is composed of 186 university students. Personal Information Form, Honor Concept Perception Toward Women Scale, Schwartz’s Value Survey, Bern Sex Role Inventory were used to collect data. Honor Concept Perception Toward Women Scale has three components: traditional honor concept, egalitarian attitude, premarital sex/honor concept. Schwartz Value Survey has ten types of values and two components of higher-order values: Types of values; power, achievement, hedonism, stimulation, self-direction, universalism, benevolence, tradition, conformity, security. Components of higher-order values; Openness to Change/Conservation, Self- Transcendence/Self- Enhancement. Bern Sex Role Inventory has three components: feminity, masculinity and socıal desirability. This study, Multiple Linear Regression and Independent Samples T-Test were used to analyze the data. At the end of the study, there was significant diffrence between women and men according to traditional honor concept and egalitarian attitude; unsversalism value and benevolence value; feminity sex roles and masculinity sex roles. Women had higher score on egalitarian attitude, unsversalism, benevolence values and feminity sex roles than men. Men had higher score on traditional honor concept and masculinity sex roles than women. Sex and importance of religion variables significantly predicted traditional honor concept. Sex,importance of religion, universalism and power significantly predicted egalitarian attitude .